2021
DOI: 10.1186/s13054-021-03705-3
|View full text |Cite
|
Sign up to set email alerts
|

Association between the use of balanced fluids and outcomes in critically ill children: a before and after study

Abstract: Background Hyperchloremia and chloride load have been associated with worse clinical outcomes in critically ill patients. We sought to evaluate the electrolyte profile and clinical outcomes associated with a unit-wide transition from saline to balanced fluids for resuscitation and maintenance fluids in a pediatric intensive care unit (PICU). Methods A before and after analysis of all patients admitted to the PICU in a large, urban, academic hospita… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 25 publications
0
9
0
1
Order By: Relevance
“…Steppan et al (26) found a significant elevation of syndecan-1 levels in adult patients with sepsis following abdominal surgery, which was correlated with increased plasma levels of inflammatory biomarkers. Barhight et al (9) found a before-versus-after study of a change in fluid protocol using various crystalloids, an association with greater frequency of hyperchloremia (15.5% vs 10.4%; p < 0.0001) with the use of UBFs. Fernández-Sarmiento et al (8) found a greater odds of acute kidney injury and the need for renal replacement therapy in children with sepsis in association with fluid resuscitation with UBFs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Steppan et al (26) found a significant elevation of syndecan-1 levels in adult patients with sepsis following abdominal surgery, which was correlated with increased plasma levels of inflammatory biomarkers. Barhight et al (9) found a before-versus-after study of a change in fluid protocol using various crystalloids, an association with greater frequency of hyperchloremia (15.5% vs 10.4%; p < 0.0001) with the use of UBFs. Fernández-Sarmiento et al (8) found a greater odds of acute kidney injury and the need for renal replacement therapy in children with sepsis in association with fluid resuscitation with UBFs.…”
Section: Discussionmentioning
confidence: 99%
“…These children with hyperchloremia also had a greater risk of acute kidney injury associated with endothelial glycocalyx alterations 6 hours after receiving UBFs (9/15 vs 6/15; OR, 1.7; 95% CI, 1.12-3.18). In this regard, the patients with acute kidney injury had a longer PICU stay than those without kidney injury (11 d [IQR,(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)] vs 8 d [5-14 d], respectively; p = 0.03). Likewise, we found that patients who received UBF boluses and had metabolic acidosis, hyperchloremia, and an elevated PBR at time 2 had a greater risk of developing acute kidney injury (11/16 vs 5/16; aOR, 4.39; 95% CI, 1.28-14.98; p = 0.01).…”
Section: Clinical Abnormalities According To the Type Of Crystalloid ...mentioning
confidence: 98%
See 1 more Smart Citation
“…19 The average hourly IVF rate received by each patient was compared to their estimated weight-based maintenance IVF (mIVF) rate, calculated using the Holliday-Segar method ("4-2-1 rule"), 20 because this period aligns with the resuscitation and stabilization phase of care. 21 New oxygen requirement was defined as documented supplemental oxygen above baseline requirement. ACS was identified using established criteria of pulmonary infiltrate on chest x-ray along with fever or respiratory symptoms.…”
Section: Demographics and Clinical Variablesmentioning
confidence: 99%
“…In all other situations, balanced crystalloids are suggested as first-line crystalloids, especially in pediatric sepsis [ 13 , 17 ]. They should be used with caution in cases of anuria, although hyperkaliemia does not contraindicate their use in critically ill children [ 52 ]. Indeed, balanced crystalloids do not generate higher kalemia, because their [K + ] content is rapidly diluted in the extracellular fluid and the [K + ] shifting out of cells induced by normal saline-related hyperchloremic metabolic acidosis is much greater [ 53 , 54 ].…”
Section: Rationalementioning
confidence: 99%